The Effectiveness of Using Electronic Modules in Mathematics Subjects in the Material of Constructing Flat Sided Space - Maulana, Muhammad Natsir; Muslim, Suyitno; Sukardjo, Moch (Journal of Education Reseach and Evaluation, 2022)
Current technological developments encourage the development of many electronic modules that affect the learning process. The problem of learning mathematics obtained lies in learning outcomes that are not optimal, one of the causes is the lack of learning resources used and limited study time. With the use of electronic modules, material can be presented in various ways, giving students the flexibility to study independently without being bound by time and place. So that it allows students to improve their learning outcomes. The purpose of this study was to test the effectiveness of the electronic module on cognitive learning outcomes in the flat-sided wake-up material. The research approach used is quantitative. The type of research used is pre-Experimental. The design used in this research is One Group Pretest-Posttest. The research subjects were class VIII students, totalling 32 students with 14 males and 18 females. Methods of data collection by observation, interviews, and tests. The test instrument used was in the form of an objective test with a total of 10 items. The analysis of improving learning outcomes was analyzed using the N-Gain formula. N-Gain is used to calculate the increase in learning outcomes. Based on the N-gain analysis, student learning outcomes show a value of 0.61 or in percent is 61% with a fairly effective category. So learning by using the electronic mathematics module is quite effective in improving students' mathematics learning outcomes.